Conceptual metaphors of sexual intercourse in Thai Yaoi fiction - Narongkan Rodsap; Methus Siriwat (Cogent Arts & Humanities)
This study aimed to analyze the conceptual metaphors of sexual intercourse in Thai Yaoi fiction as well as analyze the conceptual system of Thai language users from the usage of metaphors following the Cognitive Semantics guideline. The study was conducted by analyzing Thai texts from 40 online Yaoi novels, 10 published Yaoi fiction stories and 5 short Yaoi novels published between 2010 and 2020. The concepts of Data were analyzed based on the conceptual metaphor. The findings showed 14 types of conceptual metaphors for sexual intercourse in Thai Yaoi fiction, including conceptual metaphors of traveling, conceptual metaphors of doing exercise and playing sport, conceptual metaphors of food, conceptual metaphors of supernatural powers, conceptual metaphors of valuables, conceptual metaphors of war, conceptual metaphors of object, conceptual metaphors of animal, conceptual metaphors of humans, conceptual metaphors of plants, conceptual metaphors of liquid, conceptual metaphors of fire, conceptual metaphors of career and conceptual metaphors of natural phenomena. These conceptual metaphors reflect the concepts of Sexual Intercourse in Thai Yaoi Fiction in 2 forms, which were ontological correspondence and epistemic correspondence.